Łódzka polonistyka uniwersytecka w latach sześćdziesiątych i siedemdziesiątych - Pusz, Wiesław (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2013)
The article is a polemic with selected theses on the condition of Łódź Polish Studies, put forward by Professor Krystyna Poklewska in an interview published in the first issue of “Czytanie Literatury”.